Storyboards : motion in art - Simon, Mark , 1964- (Focal, 2007)
The storyboard is the visual blueprint of a film or television project before it is shot. The director's vision is illustrated in the manner of a comic strip and handed on to the crew for purposes of budgeting, design, and communication. Using exercises, real-life examples of working in the entertainment industry, interviews with people in the industry, and sample storyboard drawing, this book will teach you how to: develop and improve your boards; work with directors; develop your resume and your portfolio; market your talent; create and improve a storyboard using computers. New to this edition: full color; feature samples from top storyboard artists; 20 new chapters reflecting latest industry knowledge; more information on the artistic side of storyboarding; and brand new art throughout, including storyboards from The Simpsons, The West Wing, Captain Scarlet, seaQuest DSV, and The Matrix.--From publisher description